Anne Michaels e le ferite del linguaggio (Altre Modernità, 2014)
The essay starts with a brief introduction on Jewish Canadian writers, and especially on Jewish women poets and novelists, who have only recently found a proper critical attention. On the literary map of Jewish Canadian women writers, the Shoah occupies a specific space, as in the novel Fugitive Pieces by Anne Michaels, published in 1996. A poet and novelist, the Canadian writer revisits the Shoah through the voice of a male survivor, Jakob Beer, rescued by a geologist, working at the Biskupin site in Poland, who literally adopts him, taking him in incognito to Greece and, after World War II, to Canada. In the second part of the novel the narration switches to Ben, a professor of meteorology in contemporary Toronto. A child of survivors, Ben does not know how to face the violence suffered by his parents until he meets Jakob.Fugitive Pieces is analysed taking into consideration its polyphonic structure, the manifold motives and threads that weave together an intricate pattern, based on historical events and personal stories. Thanks to her use of scientific language from the realm of geology, paleobotany and geography, Michaels excavates time and space, past and present, in order to find a language to unveil the atrocities of Nazism against Jews, to preserve and evoke the memories of the survivors, but at the same time lead to a possible reconciliation with the past.